Análise numérico-experimental da dispersão de poluentes e da geometria da chama de poças de diesel e biodiesel - Salvagni, Rafael Gialdi (Universidade do Vale do Rio dos Sinos, 2017)
This work presents a numerical-experimental study of pollutants dispersion and flame geometry in a pool fire. Combustion modeling in a pool fire with plume dispersion as a function of the incident wind is carried out with the objective of phenomenon characterization. A laboratory-scale wind tunnel is used to perform the experimental analysis of diesel (S-500) and biodiesel (B-100) pool fire in a cylindrical tank with a reduced size of Ø110 x 57.4 mm. In addition, the FDS software was used to analyze and compare the results, using a model in a scale of the same magnitude of the experimental setup. The wind speed influence on the flame geometry – tilt angle, height and length – was analyzed as well as other questions related to the structure of the flame, such as dimensionless flame and plume temperature and outer layer temperature. Finally, an analysis of the mass burning rate was done to complement the experimental data and to obtain more information about the flame behavior. The data obtained were applied in the semi-empirical correlations of flame length and tilt angle to compare their behavior with the prediction of other authors. It Was observed that the change of flame geometry induces a change of plume position and dispersion. The behavior of the flame geometry was observed; the angle changes proportionally to the air flow speed. The variation in flame height and length was inversely proportional to air flow speed. The angle tilt and height agreed with the literature, but the length presented differences. The temperature of the flame increased with increasing of air flow speed being the values for biodiesel 49% higher than for diesel. The plume temperature presented a decrease with the increase of air flow speed, temperatures for diesel were about 110% smaller than for biodiesel. The same trend occurred with the measured outer layer temperature that reduced as the pool fire measurement distance increased, with a 20.3% difference between the fuels. The mass burning rate was governed by different mechanisms of heat feedback and buoyancy, which caused different behaviors for diesel and biodiesel, with diesel mass burning rates being higher in general. The experimental data obtained were compared with the results of the numerical analysis performed in the FDS software, and thus the numerical validation was done. The simulated results for tilt angle length, height and temperature of the plume and the outer layer agree well with experimental ones. The flame temperatures show an inverse trend in relation to experimental data. Pollutant dispersion analyzes showed a trend of abrupt reduction of concentration with increasing distance at lower air flow speed and a smoother and steady reduction at higher speeds, yet presenting a large discrepancy in relation to the numerical values for both fuels.
Keywords: Incêndio em poça; Dispersão de poluentes; FDS; Diesel; Biodiesel; Pool fire; Pollutants dispersion; FDS; Diesel; Biodiesel; ACCNPQ::Engenharias::Engenharia Mecânica